2011
DOI: 10.1002/star.201100081
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acid treatment on the physicochemical and structural characteristics of starches from different botanical sources

Abstract: Starch and starch derivatives (maltodextrins) are used as encapsulating materials. Starch for use as encapsulating material could be subjected to mild acid treatment. However, the granule size and organization of starch components (AM and AP) play an important role in the acid treatment. The aim of this research was to produce modified starch that might be used as encapsulate material, applying moderate acid-treatment with 3 N sulphuric acid in a ratio 1:5 w/v for 3 h at 608C, in starches from different granul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 30 publications
1
24
0
1
Order By: Relevance
“…Viscosities reduction in Ann was similar to that of HMT-30. The decrement in breakdown viscosity proved that CBS modified by ANN and HMT was stable during continued heating and shearing, which was in conformity with previous studies (Palma-Rodriguez et al, 2012;Zavareze & Dias, 2011).…”
Section: Pasting Propertiessupporting
confidence: 91%
“…Viscosities reduction in Ann was similar to that of HMT-30. The decrement in breakdown viscosity proved that CBS modified by ANN and HMT was stable during continued heating and shearing, which was in conformity with previous studies (Palma-Rodriguez et al, 2012;Zavareze & Dias, 2011).…”
Section: Pasting Propertiessupporting
confidence: 91%
“…The gelatinization properties of raw and toasted maize flour were analyzed by differential scanning calorimetry (TA Instruments, Q2000, New Castle, DE, USA) previously calibrated with indium following the procedure described by Palma-Rodriguez et al (2012) with slight modifications. A flour sample (3.0 mg dry basis) was weighed in an aluminium pan and deionized water (6.0 L) was added.…”
Section: Differential Scanning Calorimetry (Dsc)mentioning
confidence: 99%
“…ModMS microcapsules showed significantly lower surface AA % than the ModRS and ModPS microcapsules (Table 1). These results can be probably be associated with the amylose contents of these starches, which is considerably higher in modified maize starch than in modified potato and rice starches 31. One part of the total AA retained in the microcapsules was localized in the surface.…”
Section: Resultsmentioning
confidence: 90%
“…Thus, the differences in moisture content could be attributed to the structure of granules and viscosity of starches. Palma‐Rodríguez et al 31 reported that NRS had a more rigid or tight crystalline structure and higher viscosity than acid the acid‐ModS, influencing the rate of drying 33. It should be remarked that a low a w in the microcapsules is desirable for achieving longer shelf‐life.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation